Sustainable Digital Accounting Transformation: A Strategy for Strengthening Financial Governance to Elevate MSMEs - Jennisa Dwina Indriani; Rusliza Binti Yahaya; Noor Lela Binti Ahmad; Sri Kemala; Sri Asyrafil Mustaqmah; Mirawati; Yeni Melia (LKP KARYA PRIMA KURSUS, 2026)
This study aims to analyze the implementation of the SIAPIK application-based digital accounting system to support business upgrading among MSMEs in Bukittinggi. The research is motivated by the persistently low quality of financial recording in MSMEs and the growing need for digital transformation to achieve effective, transparent, and sustainable business management. A qualitative case study design was employed to gain an in-depth understanding of the phenomenon. The research informants consisted of 15 MSME practitioners selected through purposive sampling, based on the criteria of being registered entities, possessing a Taxpayer Identification Number (NPWP), and having operated for over 2 years. Data were collected via semi-structured interviews, participatory observation, and documentation, and subsequently analyzed using the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. The findings reveal four major themes: SIAPIK as an instrument for business regularity, digitalization as a strategy for business upgrading, challenges in digital literacy and technological adaptation, and digital accounting as a driver for business sustainability. The use of the SIAPIK application assists MSMEs in enhancing financial administration, operational efficiency, and informed decision-making, as well as facilitating access to financing and business legality. However, its implementation still encounters obstacles, such as limited technological proficiency and a lack of digitalization mentoring. This research contributes to the development of sustainable accounting discourse and MSME digital transformation, providing practical implications for the reinforcement of digital literacy programs and specialized mentoring in the use of the SIAPIK application.